Investigating the Impact of Future Anxiety on Life Satisfaction among Students Receiving Education in the Faculty of Sports Sciences - Namlı, Aysel Kızılkaya; Tan, Çetin; Dalga, Dilay Dalga Dilay (My University, 2026)
The aim of this study is to examine the effect of future anxiety levels on life satisfaction among students of the Faculty of Sports Sciences. The research was designed using a quantitative method approach and conducted with a sample group of 190 students from the Faculty of Sports Sciences at Fırat University. The participants were selected using a purposive sampling method. The data were collected through the Satisfaction with Life Scale and the Future Anxiety Scale for University Students. The findings revealed a significant negative relationship between students’ life satisfaction levels and their future anxiety levels. Furthermore, no significant differences were found in future anxiety or life satisfaction scores based on gender, year of study, department, or age.
Keywords: Eğitim; Eğitim Araştırmaları; Spor Bilimleri; Psikoloji